Do school preferences differ between mothers and fathers? International evidence from PISA - Jerrim, John; Prieto-Latorre, Claudia; Lopez-Agudo, Luis Alejandro; Marcenaro-Gutiérrez, Óscar David (Taylor & Francis, 2023)
A sizeable literature – spanning education, sociology and economics – has investigated the issue of parental school preferences and school choice. A notable gap in the existing evidence base is an exploration of how such preferences differ between mothers and fathers. We present new cross-national findings on this matter, drawing on survey data collected from more than 300,000 parents across 25 countries. Our findings suggest that mothers rate the school environment – whether the school is safe and has a pleasant atmosphere – to be more important than fathers. Differences are also observed with respect to the school’s reputation and whether it has a high level of achievement. Clearer evidence of such differences emerges for industrialised Western nations than for countries that are not members of the OECD. In most countries, mothers’ and fathers’ preferences do not vary substantially between sons and daughters.
Keywords: Educación; PISA; School choice; School preferences